To include or exclude? Marginalization of the deformed in the Classical Greek World - Sulosky Weaver, Carrie L. (Journal of Greek Archaeology, 2019)
In the Classical period (c. 480–323 BC), the ideal Athenian citizen was kalos kai agathos – beautiful and good (Plato Charmides 154e, Gorgias 474d–475e). In order to be both beautiful and good, the ideal citizen must embody a panoply of noble personality traits. He must be free, civic-minded, selfless, courageous, loyal, honorable, helpful, truthful, hardworking, just, careful, practical, intelligent, reasonable, self-controlled, and moderate in all things. In addition to these intangible qualities, the ideal citizen must also possess important tangible ones: physical beauty and perfection.